PERAN GURU PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PEMBELAJARAN SEJARAH DI SMA NEGERI 6 SAMARINDA - ani, fitri (Jurnal Pendidikan Sejarah Indonesia, 2025)
This study discusses the role of the driving teacher in implementing the independent curriculum for history learning at SMA Negeri 6 Samarinda, which has several objectives, namely; to find out the role of the driving teacher in implementing the independent curriculum for history learning for students at SMA Negeri 6 Samarinda, and to find out the obstacles faced by the driving teacher in implementing the independent curriculum for history learning at SMA Negeri 6 Samarinda. The type of research used is qualitative research. Qualitative research focuses on collecting qualitative data such as words, pictures, behavior, and documents, with the aim of describing and understanding the phenomena that occur thoroughly. Data collection techniques are interviews, observation (observation or recording), and documentation. In this study, the analysis used was data collection, data presentation, and conclusion drawing. The results of this study reveal that the role of the driving teacher in implementing the independent curriculum for history learning has several stages. The first stage is learning planning, the second is implementing learning in a differentiated manner, and the third is evaluating. In addition, the driving teacher shares good practices in educational forums, establishes collaboration between teachers with the aim of increasing students' interest in learning, and realizes student leadership by giving responsibility to students to lead the group. In carrying out their role, motivating teachers also face various obstacles including; difficulties in achieving learning objectives, difficulties in innovating, inadequate facilities and infrastructure, high dependence on technology, and lack of funds that support learning activities.